Dual diagnosis capability in mental health and addiction treatment services: An assessment of programs across multiple state systems - McGovern, Mark P. (2014)
Despite increased awareness of the benefits of integrated services for persons with co-occurring substance use and psychiatric disorders, estimates of the availability of integrated services vary widely. The present study utilized standardized measures of program capacity to address co-occurring disorders, the Dual Diagnosis Capability in Addiction Treatment (DDCAT) and Dual Diagnosis Capability in Mental Health Treatment (DDCMHT) indexes, and sampled 256 programs across the United States. Approximately 18% of addiction treatment and 9% of mental health programs met criteria for dual diagnosis capable services. This is the first report on public access to integrated services using objective measures.